PENGARUH TAMBAHAN PENGHASILAN PEGAWAI, KOMITMEN ORGANISASI DAN KEAHLIAN TEKNOLOGI INFORMASI TERHADAP KINERJA TENAGA ADMINISTRASI SEKOLAH MENENGAH PERTAMA ( SMP) PADA MASA PANDEMI COVID 19 DI KABUPATEN PURWAKARTA - Patoni Patoni (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
Patoni, (2021). The Effect of Additional Employee Income, Organizational Commitment and Information Technology Expertise on the Performance of School Administration Personnel During the Covid 19 Pandemic in Purwakarta Regency. The purpose of this study was to determine the effect of additional employee income, organizational commitment and information technology expertise on the performance of junior high school (SMP) administrative personnel during the Covid 19 Panedmi era in Purwakarta Regency. The research method used was descriptive analytical. The research data were obtained from questionnaires distributed directly to 90 school administration personnel with the status of state civil servants throughout Purwakarta Regency spread across 53 SMPNs via google form, and data processing was carried out using the SPSS version 23.0 program. The results showed that partially additional employee income has a significant effect on the performance of junior high school administration staff in Purwakarta district by 32.42%, organizational commitment has an effect of 16.32 and information technology expertise has a significant effect on the performance of junior high school administration staff in Purwakarta district by 36 , 50%. Simultaneously, the significant effect of additional employee inclusion, organizational commitment and information technology expertise on the performance of junior high school administration staff in Purwakarta Regency is 56.70% and the remaining 43.30% is influenced by other factors not examined by the researcher.